Simplify 1)begin{bmatrix}4 & 5 end{bmatrix}+begin{bmatrix}6 & -4 end{bmatrix} 2)begin{bmatrix}4 & -13&3-5&-4 end{bmatrix}-begin{bmatrix}4 & -23&6-5&-6 end{bmatrix} 3)begin{bmatrix}4 & -16&-3 end{bmatrix}+begin{bmatrix}5 & -65&-5 end{bmatrix}-begin{bmatrix}-2 & 0-2&-6 end{bmatrix} Solve for x and y begin{bmatrix}-10 & -4x&-1 end{bmatrix}+begin{bmatrix}-5 & 8y&-10 end{bmatrix}=begin{bmatrix}-15 & x16&-11 end{bmatrix}

Simplify 1)begin{bmatrix}4 & 5 end{bmatrix}+begin{bmatrix}6 & -4 end{bmatrix} 2)begin{bmatrix}4 & -13&3-5&-4 end{bmatrix}-begin{bmatrix}4 & -23&6-5&-6 end{bmatrix} 3)begin{bmatrix}4 & -16&-3 end{bmatrix}+begin{bmatrix}5 & -65&-5 end{bmatrix}-begin{bmatrix}-2 & 0-2&-6 end{bmatrix} Solve for x and y begin{bmatrix}-10 & -4x&-1 end{bmatrix}+begin{bmatrix}-5 & 8y&-10 end{bmatrix}=begin{bmatrix}-15 & x16&-11 end{bmatrix}

Question
Matrices
asked 2021-02-11
Simplify
1)\(\begin{bmatrix}4 & 5 \end{bmatrix}+\begin{bmatrix}6 & -4 \end{bmatrix}\)
2)\(\begin{bmatrix}4 & -1\\3&3\\-5&-4 \end{bmatrix}-\begin{bmatrix}4 & -2\\3&6\\-5&-6 \end{bmatrix}\)
3)\(\begin{bmatrix}4 & -1\\6&-3 \end{bmatrix}+\begin{bmatrix}5 & -6\\5&-5 \end{bmatrix}-\begin{bmatrix}-2 & 0\\-2&-6 \end{bmatrix}\)
Solve for x and y
\(\begin{bmatrix}-10 & -4\\x&-1 \end{bmatrix}+\begin{bmatrix}-5 & 8\\y&-10 \end{bmatrix}=\begin{bmatrix}-15 & x\\16&-11 \end{bmatrix}\)

Answers (1)

2021-02-12
Step 1 To solve the given matrices. Step 2 Given that 1)\(\begin{bmatrix}4 & 5 \end{bmatrix}+\begin{bmatrix}6 & -4 \end{bmatrix}\)
\(\begin{bmatrix}4+6 & 5-4 \end{bmatrix}\)
\(\begin{bmatrix}10 & 1 \end{bmatrix}\)
\(\therefore \begin{bmatrix}4 & 5 \end{bmatrix}+\begin{bmatrix}6 & -4 \end{bmatrix}=\begin{bmatrix}10 & 1 \end{bmatrix}\)
2)\(\begin{bmatrix}4 & -1\\3&3\\-5&-4 \end{bmatrix}-\begin{bmatrix}4 & -2\\3&6\\-5&-6 \end{bmatrix}\)
\(\begin{bmatrix}4-4 & -1+2\\3-3&3-6\\-5+5&-4+6 \end{bmatrix}=\begin{bmatrix}0 & 1\\0&-3\\0&2 \end{bmatrix}\)
\(\therefore \begin{bmatrix}4 & -1\\3&3\\-5&-4 \end{bmatrix}-\begin{bmatrix}4 & -2\\3&6\\-5&-6 \end{bmatrix}=\begin{bmatrix}0 & 1\\0&-3\\0&2 \end{bmatrix}\)
3)\(\begin{bmatrix}4 & -1\\6&-3 \end{bmatrix}+\begin{bmatrix}5 & -6\\5&-5 \end{bmatrix}-\begin{bmatrix}-2 & 0\\-2&-6 \end{bmatrix}\)
\(\begin{bmatrix}4+5+2 & -1-6-0\\6+5+2&-3-5+6 \end{bmatrix}\)
\(\begin{bmatrix}3 & -5\\13&-2 \end{bmatrix}\)
\(\therefore \begin{bmatrix}4 & -1\\6&-3 \end{bmatrix}+\begin{bmatrix}5 & -6\\5&-5 \end{bmatrix}-\begin{bmatrix}-2 & 0\\-2&-6 \end{bmatrix}=\begin{bmatrix}3 & -5\\13&-2 \end{bmatrix}\)
Given that
\(\begin{bmatrix}-10 & -4\\x&-1 \end{bmatrix}+\begin{bmatrix}-5 & 8\\y&-10 \end{bmatrix}=\begin{bmatrix}-15 & x\\16&-11 \end{bmatrix}\)
\(\begin{bmatrix}-10-5 & -4+8\\x+y&-1-10 \end{bmatrix}=\begin{bmatrix}-15 & x\\16&-11 \end{bmatrix}\)
\(\begin{bmatrix}-15 & 4\\x+y&-11 \end{bmatrix}=\begin{bmatrix}-15 & x\\16&-11 \end{bmatrix}\)
Equating on both sides we have
x=4
x+y=16
Since x=4 then 4+y=16
y=12
\(\therefore x=4 \text{ and } y=12\)
0

Relevant Questions

asked 2020-10-25

Solve for X in the equation, given
\(3X + 2A = B\)
\(A=\begin{bmatrix}-4 & 0 \\1 & -5\\-3&2 \end{bmatrix} \text{ and } B=\begin{bmatrix}1 & 2 \\ -2 & 1 \\ 4&4 \end{bmatrix}\)

asked 2020-12-16
Compute the following
a) \begin{bmatrix}-5 & -4&3&-10&-3&6 \\6&-10&5&9&4&-1 \end{bmatrix}+\begin{bmatrix}-7 & 3&10&0&8&8 \\8&0&4&-3&-8&0 \end{bmatrix}
b) -5\begin{bmatrix}8 & -10&7 \\0 & -9&7\\10&-5&-10\\1&5&-10 \end{bmatrix}
c)\begin{bmatrix}3 & 0&-8 \\6 & -4&-2\\6&0&-8\\-9&-7&-7 \end{bmatrix}^T
asked 2021-01-28
Write out the system of equations that corresponds to each of the following augmented matrices:
(a)\(\begin{pmatrix}3 & 2&|&8 \\1 & 5&|&7 \end{pmatrix}\)
(b)\(\begin{pmatrix}5 & -2&1&|&3 \\2 & 3&-4&|&0 \end{pmatrix}\)
(c)\(\begin{pmatrix}2 & 1&4&|&-1 \\4 & -2&3&|&4 \\5 & 2&6&|&-1 \end{pmatrix}\)
(d)\(\begin{pmatrix}4 & -3&1&2&|&4 \\3 & 1&-5&6&|&5 \\1 & 1&2&4&|&8\\5 & 1&3&-2&|&7 \end{pmatrix}\)
asked 2020-11-27
Given \(B=\begin{bmatrix}-3 & -3 \\1 & -2 \end{bmatrix} \text{ and } C=\begin{bmatrix}-15 & -6 \\1 & 10 \end{bmatrix}\)
Solve \(3X+B=C\)
X=?
asked 2020-12-16
Consider the matrices
\(A=\begin{bmatrix}1 & -1 \\0 & 1 \end{bmatrix},B=\begin{bmatrix}2 & 3 \\1 & 5 \end{bmatrix},C=\begin{bmatrix}1 & 0 \\0 & 8 \end{bmatrix},D=\begin{bmatrix}2 & 0 &-1\\1 & 4&3\\5&4&2 \end{bmatrix} \text{ and } F=\begin{bmatrix}2 & -1 &0\\0 & 1&1\\2&0&3 \end{bmatrix}\)
a) Show that A,B,C,D and F are invertible matrices.
b) Solve the following equations for the unknown matrix X.
(i) \(AX^T=BC^3\)
(ii) \(A^{-1}(X-T)^T=(B^{-1})^T\)
(iii) \(XF=F^{-1}-D^T\)
asked 2021-03-12
Let a linear sytem of equations Ax=b where
\(A=\begin{pmatrix}4 & 2&-2 \\2 & 2&-3\\-2&-3&14 \end{pmatrix} , b=\begin{pmatrix}10 , 5 , 4 \end{pmatrix}^T\)
in case we solve this equation system by using Dolittle LU factorization method , find Z and X matrices
asked 2021-05-04
Solve the system Ax = b using the given LU factorization of A
\(A=\begin{bmatrix}-2 & 1 \\2 & 5 \end{bmatrix}=\begin{bmatrix}1 & 0 \\-1 & 1 \end{bmatrix}\begin{bmatrix}-2 & 1 \\0 & 6 \end{bmatrix}, b=\begin{bmatrix}5 \\1 \end{bmatrix}\)
asked 2021-02-24
The product of matrix B and C is matrix D
\(\begin{bmatrix}2 & -1&4 \\g & 0&3\\2&h&0 \end{bmatrix} \times \begin{bmatrix}-1 & 5 \\4&f\\-3&1 \end{bmatrix}=\begin{bmatrix}i & 24 \\-16&-4\\4&e \end{bmatrix}\)
3.From the expression above, what should be the value of e?
4.From the expression above, what should be the value of g?
5.From the expression above, what should be the value of f?
asked 2021-01-13
Find A+B
\(A=\begin{bmatrix}7 & -1 \\2 & 9 \\ -7 & -8 \end{bmatrix} ,B=\begin{bmatrix}2 & 5 \\-9 &0 \\ 8 & 6 \end{bmatrix}\)
a) \(\begin{bmatrix}5 & 4 \\11 & 9 \\ -15 & -2 \end{bmatrix}\)
b) \(\begin{bmatrix}5 & -6 \\11 &9 \\ -15 & -14 \end{bmatrix}\)
c) \(\begin{bmatrix}9 & -6 \\-7 & 9 \\ 1 & -14 \end{bmatrix}\)
d) \(\begin{bmatrix}9 & 4 \\-7 &9 \\ 1 & -2 \end{bmatrix}\)
asked 2020-10-18
Find x,y,z and w
\(\begin{bmatrix}x & 5&(2x-1) \\y & 4 & 4y \end{bmatrix}=\begin{bmatrix}(2x-3) & z&5 \\7 & (2+1)&(3y+7) \end{bmatrix}\)
...